2006
DOI: 10.1016/j.virusres.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Cap-independent translation of plant viral RNAs

Abstract: The RNAs of many plant viruses lack a 5′ cap and must be translated by a cap-independent mechanism. Here, we discuss the remarkably diverse cap-independent translation elements that have been identified in members of the Potyviridae, Luteoviridae, and Tombusviridae families, and genus Tobamovirus. Many other plant viruses have uncapped RNAs but their translation control elements are uncharacterized. Cap-independent translation elements of plant viruses differ strikingly from those of animal viruses: they are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 93 publications
(144 reference statements)
0
117
0
1
Order By: Relevance
“…In contrast, BYDV must employ an alternate means of cap-independent translation. Host translation machinery recruitment to the viral mRNA is aided by structures present in 5Ј-and/or 3Ј-UTRs of the mRNAs instead of a 5Ј cap/poly(A) tail (15). For cap-dependent translation initiation, a significant, central role is played by eIF4F.…”
Section: Barley Yellow Dwarf Virus (Bydv)mentioning
confidence: 99%
“…In contrast, BYDV must employ an alternate means of cap-independent translation. Host translation machinery recruitment to the viral mRNA is aided by structures present in 5Ј-and/or 3Ј-UTRs of the mRNAs instead of a 5Ј cap/poly(A) tail (15). For cap-dependent translation initiation, a significant, central role is played by eIF4F.…”
Section: Barley Yellow Dwarf Virus (Bydv)mentioning
confidence: 99%
“…Translation initiation factor eIF4G binds the 3Ј-BTE with high affinity (24,32) and protects SL-I from modification by SHAPE reagents (33). The loop of stemloop III (3Ј-SL-III) of the 3Ј-BTE forms a long distance RNA-RNA "kissing" stem-loop base-pairing interaction with a loop in the 5Ј-end of the mRNA (25,34) (Fig. 1C).…”
mentioning
confidence: 99%
“…PAP binds to VPg at a different site from the eIFiso4F/eIF4F binding site. The effect of VPg on the depurination of selected RNA molecules, including structured RNA derived from TEV (33)(34)(35), showed that VPg decreases depurination of RNAs and competes with IRES containing TEV RNA for PAP binding. These findings correlate with the inhibition of PAP enzymatic activity by VPg in wheat germ lysate.…”
Section: Pokeweed Antiviral Protein (Pap)mentioning
confidence: 99%